PERAN DARI UNITED NATIONS DEVELOPMENT PROGRAMME (UNDP) DALAM MENANGGULANGI KEMISKINAN ETNIS TAMIL DI SRI LANKA - Wira Sudewa, I Putu Agung; Priadarsini, Ni Wayan Rainy; widya nugraha, A.A. Bagus Surya (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2015)
ABSTRACT This research aims to answer research question about the role of United Nations Development Programme to eradicated poverty on Tamil ethnic. The aspect of poverty eradication is seen from peace building viewpoint. This research uses qualitative method to analysis data. All data source from this research is secondary source that got mainly from news, book, and e-book. The finding of this research is the role of poverty eradication that UNDP was implemented using people centered-development approach. Besides that UNDP is also prioritize gender empowerment in every aspect of their programs. Overall the program that UNDP has done is quite success to eradicated poverty but this program was less successful in addressing the root of discrimination. Keywords : Tamil ethnic, poverty, peace building, people centered development, UNDP